Phytochemical Screening and In Vitro Antioxidant and Anti-inflammatory Activities of Aerial Parts of Euphorbia hirta L. - Basyal, Deepak; Neupane, Astha; Pandey, Durga Prasad; Pandeya, Shiva (Journal of Nepal Chemical Society, 2021)
Euphorbia hirta L (Euphorbiaceae) also called asthma herb has long been prescribed in traditional medicine because it exhibits diverse pharmacological actions due to the presence of alkaloids, flavonoids, polyphenols, triterpenoids, and saponins. The present study is aimed at the study of phytochemical and antioxidant activity and anti-inflammatory screening of E. hirta. Extraction of dried powder was performed followed by phytochemical screening using color reactions. Total phenolic content (TPC) and total flavonoid content (TFC) of the extracts were estimated by Folin-Ciocalteu and Aluminum chloride method respectively. The antioxidant activity was studied by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging method. Anti-inflammatory activity was studied by using protein denaturation in vitro bioassay. Phytochemical screening showed the presence of flavonoids, alkaloids, and phenolic compounds. TPC, TFC and antioxidant activity (IC50) of the extract were found as 288.10 mg gallic acid equivalent per gram (GAE/g), 29.36 mg quercetin equivalent per gram (QE/g) and 32.23 µg/mL (p<0.05) respectively. Diclofenac sodium and E. hirta extract showed the maximum inhibition of 91.28% and 68.20% respectively at the concentration of 1000 µg/mL compared with control (p>0.05). The phenolic compounds and flavonoids exert antioxidant and anti-inflammatory activities because of their scavenging ability. The demonstrated antioxidant and anti-inflammatory activities may be the rationale behind some of its folkloric uses and also may be responsible for some of its pharmacological effects. Thus, E. hirta can be considered a good source of antioxidants and anti-inflammatory actions, which might be beneficial for combating oxidative stress.